Peningkatan Penjualan Melalui Inovasi Label Pada Kemasan Rengginang UMKM Desa Telajung - Ainulyaqin, MH; Adrianna SR; Sakum; Hamidah, Siti; Khoerunisa, Firda (DPPM Universitas Pelita Bangsa, 2024)
This journal explores the positive impact of label innovation on Rengginang packaging on increasing sales in the context of Micro, Small and Medium Enterprises (MSMEs) in Telajung Village. This research focuses on how changing the label design on Rengginang packaging can increase consumer appeal and encourage increased sales volume. The research method involves market analysis, consumer surveys, and implementation of label innovation on several Rengginang products from local MSMEs. The research results show that label changes are able to create significant differences in consumer perceptions of products, increase visual appeal, and expand market share. This research provides insight for Telajung Village MSMEs and similar industry players regarding the importance of label innovation in product marketing strategies. The practical implication of this research is that increased sales can be achieved through appropriate investment in attractive label designs, creating a sustainable competitive advantage in local and wider markets.